Penerapan Model Problem Besed Learning pada Mata Pelajaran Akidah Akhlak di MTS Baiturrahman NW Pemepek - M. Khaerul Madjid H.; Saparudin; Emawati (Mataram University, 2026)
This study aims to describe the implementation of Problem-Based Learning (PBL) in the Aqidah Akhlak subject at MTs Baiturrahman NW Pemepek and identify its effectiveness and the obstacles encountered. The background of the study stems from the low student activity due to the dominance of lecture and memorization methods. The study used a descriptive qualitative approach with observation techniques and in-depth interviews with Aqidah Akhlak teachers. The results showed that the implementation of PBL was able to change the learning pattern to be more student-centered. Some students began to show enthusiasm in discussions, but many remained passive and relied on more active friends. The resulting project products were still simple and not optimal in terms of creativity. Teacher interviews revealed a slight improvement compared to conventional methods, but students were still shy to discuss. The main obstacles included teachers' limited mastery of PBL strategies, limited time, and uneven student readiness. Thus, the implementation of PBL has not had a significant impact on student activity, but it has great potential to increase motivation and critical thinking skills if supported by teacher training and student habituation.